Chapter 1. Introduction to post-harvest challenges and innovations - Mpagalile, Joseph; Odjo, Sylvanus (Food and Agriculture Organization of the United Nations, 2024)
Approximately 14 percent of the food produced globally is lost during post-harvest stages before reaching retail stage (FAO, 2019a). Post-harvest losses (PHL) pose significant challenges for farmers in developing regions, particularly sub-Saharan Africa (SSA). Food losses in SSA occur across a wide spectrum, including up to 50 percent of fruit and vegetables and 10 to 20 percent for grains and pulses (FAO, 2019a). In light of this, it is imperative to enhance efforts to reduce PHL, particularly among small-scale farmers. This urgency is driven by the need to bolster food availability and optimize resource utilization. Smallholder farmers, constituting the majority of farms, bear the greatest impact of PHL, underscoring the critical importance of targeted intervention. Developing smallholder agriculture through PHL mitigation can effectively reduce poverty and hunger in low-income countries. Experience has demonstrated that the causes of PHL are multifaceted and vary across different types of value chains. However, common contributing factors include insufficient investments to facilitate the adoption of improved technologies, inadequate post-harvest management practices and institutional weaknesses. Additionally, in SSA, there is a lack of well-developed mechanization hire services for post-harvest operations. This publication consists of seven chapters with primary focus on mitigating PHL in developing regions. It covers various produce such as roots and tubers, grains, fruits, and vegetables. The inclusion of case studies from the Green Innovation Centres (GIC) for the agriculture and food sector aims to showcase various innovations and their impact on post-harvest loss education, increased income and job creation. Additionally, this publication explores the role of gender in efforts to reduce loss, agribusiness and entrepreneurship, and climate change management in post-harvest and provides recommendations for further action.